The Demography of Health and Healthcare - Pol, Louis G. author. aut Link
X, 302 p.
Keywords: In this 3rd edition of the definitive work on health demography, Pol and Thomas offer an updated view of the field and a current perspective on the applications of health demography to contemporary issues. The significance of health demography within the field of population studies has continued to increase and this work provides background on the healthcare arena and systematically presents the various aspects of demography as they relate to healthcare. This addition has been streamlined to focus on the important aspects of health demography and enhanced through the addition of charts, maps and other graphics. All statistics and tables have been updated and the most current references are included. A separate chapter on morbidity has been included and the final chapter focuses on the public policy interface with health demography. Case studies and sidebars are included throughout the book to illustrate the applications of demography within the healthcare arena. Recent developments in U.S. healthcare are highlighted to give the text a very contemporary presence. "At last! ...a book on health demography which draws together these two important and useful disciplines... and provides a central resource for students as well as professionals who need access to demographic methods, measures, and concepts. ... The authors demonstrate the relevance and applicability of demographic principles to health care in a clear, thorough manner." (Applied Demography) "A well-written, effectively organized work that clarifies the role of health demography." (Choice).